Apple procyanidins promote mitochondrial biogenesis and proteoglycan biosynthesis in chondrocytes - Isao Masuda (Nature Portfolio, 2018)
Abstract Apples are well known to have various benefits for the human body. Procyanidins are a class of polyphenols found in apples that have demonstrated effects on the circulatory system and skeletal organs. Osteoarthritis (OA) is a locomotive syndrome that is histologically characterized by cartilage degeneration associated with the impairment of proteoglycan homeostasis in chondrocytes. However, no useful therapy for cartilage degeneration has been developed to date. In the present study, we detected beneficial effects of apple polyphenols or their procyanidins on cartilage homeostasis. An in vitro assay revealed that apple polyphenols increased the activities of mitochondrial dehydrogenases associated with an increased copy number of mitochondrial DNA as well as the gene expression of peroxisome proliferator-activated receptor gamma coactivator 1-α (PGC-1α), suggesting the promotion of PGC-1α-mediated mitochondrial biogenesis. Apple  procyanidins also enhanced proteoglycan biosynthesis with aggrecan upregulation in primary chondrocytes. Of note, oral treatment with apple procyanidins prevented articular cartilage degradation in OA model mice induced by mitochondrial dysfunction in chondrocytes. Our findings suggest that apple procyanidins are promising food components that inhibit OA progression by promoting mitochondrial biogenesis and proteoglycan homeostasis in chondrocytes.